Distinguishing out-of-body experiences from lucid dreaming: a phenomenological analysis - Weiler, Marina; Moreira-Almeida, Alexander; Monti, Martin M. (Frontiers in Psychology, 2025)
Despite extensive discussions, a consensus is lacking on whether out-of-body experiences (OBEs) and lucid dreams (LDs) should be considered as distinct categories of experience, and if so, what differentiates them. To address this issue, we first discussed the implications of OBEs and LDs as the same type of phenomenon. We then compiled a comprehensive list of experiential features associated with OBEs and LDs, aiming to identify a distinguishing criterion between them. We conclude that neither the previously proposed features nor the interpretation of the experience can reliably differentiate them. We suggest that disembodiment, or existing without a physical body, should be the key phenomenological feature of OBEs, regardless of other aspects of the experience. Our argument is supported by first-person reports included as supplementary material, indicated by superscript numbers. By focusing on this crucial element, we can better understand and characterize an OBE, distinguishing it from other related experiences.